2011
DOI: 10.1007/s00405-011-1566-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of vestibular schwannoma in elderly patients

Abstract: This study aimed to evaluate surgical results of vestibular schwannoma in elderly patients using a retrospective study in a Quaternary Neurotology and Skull Base Referral Center setting. The data of 232 elderly patients (above 65 years) operated on for vestibular schwannoma in the period between April 1987 and July 2009 were reviewed. Most patients were operated on via translabyrinthine approach (TLA) using transapical extension for large tumors. Other approaches used were retrosigmoid, middle cranial fossa, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Minovi et al [18] also reported on one case (1.1%) of lethal PE after DVT in a series of 89 AN patients operated on via MFA. There is a comparable rate of PE in further series with mixed approaches of 0.2%-1.1% [14,[19][20][21][25][26][27] .…”
Section: Deep Venous Thrombosismentioning
confidence: 73%
“…Minovi et al [18] also reported on one case (1.1%) of lethal PE after DVT in a series of 89 AN patients operated on via MFA. There is a comparable rate of PE in further series with mixed approaches of 0.2%-1.1% [14,[19][20][21][25][26][27] .…”
Section: Deep Venous Thrombosismentioning
confidence: 73%
“…In elderly patients, despite the fact that complete removal is the main target of the surgery, adoption of NTR or STR in selected cases can decrease neurovascular injury, improve postoperative facial nerve results, and reduce the duration of surgery. 27 In case of a regrowth following such a scenario, SRS or Gamma Knife surgery (GKS) is preferable.…”
Section: Management Algorithmmentioning
confidence: 99%
“…Although several studies have evaluated surgical and observational outcomes in the elderly, few have directly compared microsurgical outcomes between elderly and nonelderly groups. 7,8 Our primary goals were to compare the risks of microsurgical resection in patient groups stratified by age and to test the hypothesis that symptomatic tumors in elderly patients represent a variant of VS that is more aggressive in these patients than in younger adults, resulting in increased morbidity and a higher rate of recurrence after STR.…”
mentioning
confidence: 99%